PENGARUH MODAL USAHA TERHADAP PRODUKTIVITAS USAHA TEMPE PADA UMKM MAJU BERSAMA DI DESA GUNUNG MERAKSA KECAMATAN LUBUK BATANG KABUAPTEN OKU - Yopi Yunsepa; Yuniarti Anwar; Sobirin Sobirin (KOLEGIAL, 2022)
This study aims to how the influence of venture capital on the productivity of the tempeh business in Maju Bersama MSMEs in Gunung Meraksa Village, Lubuk Batang District, OKU Regency. The method in this study used a descriptive method. The data analysis technique in this study is quantitative data analysis, which is directed to answer the problem formulation or test the hypotheses that have been formulated, because the data is quantitative, the data analysis technique uses available statistical methods. The results of the study explain that there is an effect of working capital on business productivity with the results of a simple linear regression equation that is Y=5.423 + 0.752X, and the correlation value is 0.872. This shows that the relationship between the independent variable, namely business capital and the dependent variable, is very strong. While the number r square (Coefficient of Determination) is 0.760, this value indicates that the contribution of the independent variable, namely venture capital with the dependent variable, namely business productivity, simultaneously is 76% while the remaining 24% is not examined in this study. Hypothesis testing from the data obtained t-count variable X is 9.256 where the t-count value is more than the t-table value (9.256>1.703), then Ho is rejected and Ha is accepted, meaning that there is a partial influence between the variable venture capital (X) and the variable business productivity (Y) in MSMEs Forward Together in Gunung Meraksa Village.